Clinical manifestations in a Chinese girl with heterozygous de novo NAA10 variant c. 247C > T, p. (Arg83Cys): a case report - Wei, Kaiyan; Zou, Chaochun (Frontiers in Pediatrics, 2023)
The NAA10 gene encodes the catalytic subunit of the N-terminal acetyltransferase protein complex A (NatA)N-terminal acetyltransferase complex, which is supposed to acetylate approximately 40%almost half of the human proteins. After the advent of next-generation sequencing, over 36 children with missensemore variants in the NAA10 gene and 10 males with Ogden syndrome (OMIM# 300855) have been reported. Individuals with NAA10-related syndrome have a wide spectrum of clinical manifestations and the genotype-phenotype correlation is still far from being confirmed. Here, we report a three years old Chinese girl carrying a heterozygous de novo NAA10 [NM_003491: c. 247C > T, p. (Arg83Cys)] variant (dbSNP# rs387906701) (ClinVar# 208664) (OMIM# 300013.0010). The proband not only has some mild and common clinical manifestations, including dysmorphic features, developmental delay, obstructive hypertrophic cardiomyopathy, and arrhythmia, but also shows some rare clinical features such as exophthalmos, blue sclera, cutaneous capillary malformations, and adenoid hypertrophy. Our attempt is to expand the clinical phenotype associated with NAA10-related syndrome and explore genotypephenotypegenotype-phenotype correlation with such syndrome.